Fecal Sludge Management Business Model Tool - CGIAR Research Program on Water, Land and Ecosystems (2018)
The BETA version of this tool is live. This tool presents case studies on a range of business models implemented in different parts of the world across the FSM value chain, referenced from IWMI's Resource, Recovery, and Reuse Series 6 document.